Herpes Zoster Dermatome Nervus C6-C7 Pada Penderita TB-MDR : Laporan Kasus - Mitha Miftahul Jannah; Yulisna (Medula, 2020)
Herpes shingles (HZ) is an infectious disease caused by the reactivation of the varicella shingles virus (VVZ). Are localized, mainly attacking adults with a characteristic of radicular pain, unilateral, and a horde of vesicles that are dispersed according to dermatoms that are ineralized by a single sensory nerve ganglion. Factors that potentially lead to reactivation are: previous exposure to VVZ (chickenpox, vaccination), age more than 50 years, Immunocompromais state, immunosuppressive drugs, HIV/AIDS, bone marrow transplantation or organ, violence, therapy Long-term steroids, psychological stress, trauma and the act of Distinction. Incidence of HZ in children 0.74 from 1000 person per year. This incidence increased to 2.5 from 1000 people at age 20-50 (adult age), 7, from 1000 people aged more than 60 years (older adult age) and reached 10 from 1000 person per year at the age of 80. Case: reported case of Mrs. P, 55 yo with a diagnosis of herpes shingles with TB MDR with based on anamnesis and physical examination administered therapy acyclovir tab 5x800 mg PO/day for 7 days, Paracetamol tab 3x500 mg PO/day if necessary, powder salicyl 2% applied on the lesions 3x/day and given the drug TB MDR namely Cycloserin, etionamides and moxifloxacin. Conculsion: The patient showed good therapeutic results.